2012
DOI: 10.1039/c2cp23878k
|View full text |Cite
|
Sign up to set email alerts
|

Dissociation dynamics of fluorinated ethene cations: from time bombs on a molecular level to double-regime dissociators

Abstract: The dissociative photoionization mechanism of internal energy selected C(2)H(3)F(+), 1,1-C(2)H(2)F(2)(+), C(2)HF(3)(+) and C(2)F(4)(+) cations has been studied in the 13-20 eV photon energy range using imaging photoelectron photoion coincidence spectroscopy. Five predominant channels have been found; HF loss, statistical and non-statistical F loss, cleavage of the C-C bond post H or F-atom migration, and cleavage of the C=C bond. By modelling the breakdown diagrams and ion time-of-flight distributions using st… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

4
102
1

Year Published

2013
2013
2020
2020

Publication Types

Select...
4
2

Relationship

4
2

Authors

Journals

citations
Cited by 42 publications
(107 citation statements)
references
References 67 publications
(163 reference statements)
4
102
1
Order By: Relevance
“…9 The ν 4 harmonic frequency of 1552 cm −1 ( Figure 2) is in excellent agreement with the B3LYP prediction of 1561 cm −1 . Discrepancies in the energies between the simulated and the experimental spectra towards higher eV are due to anharmonicity which is disregarded in the harmonic model of FCfit.…”
Section: Monofluoroethenesupporting
confidence: 66%
See 4 more Smart Citations
“…9 The ν 4 harmonic frequency of 1552 cm −1 ( Figure 2) is in excellent agreement with the B3LYP prediction of 1561 cm −1 . Discrepancies in the energies between the simulated and the experimental spectra towards higher eV are due to anharmonicity which is disregarded in the harmonic model of FCfit.…”
Section: Monofluoroethenesupporting
confidence: 66%
“…We based this conclusion predominantly on the correlation of the F-loss fragment ion signal with features of the TPES, indicating isolated state behaviour, in agreement with previous observations. [10][11][12][13] However, we also found that the internal energy distribution of the F-loss daughter ion C 2 F 3 + from C 2 F 4 + can be modelled assuming a purely statistical dissociation on theà electronic state of the parent ion, 9 contrary to previous reports which invoked impulsive processes.…”
Section: Introductioncontrasting
confidence: 50%
See 3 more Smart Citations